Ophrys apifera Huds. (Orchidaceae), a new orchid species to the flora of Poland - Osiadacz, Barbara; Kręciała, Mirosław (Biodiversity: Research and Conservation, 2015)
The paper provides data on the first locality of Ophrys apifera Huds. s. str. in Poland. Information about its geographical distribution and ecological features is given. A newly discovered population, found in a worked-out dolomite quarry near Imielin (Silesian Upland), is described and illustrated, as also, O. apifera is compared with O. insectifera L.